Cambiar paradigmas: una experiencia en educación superior - Alvarado Chacón, Vanesa (2004)
This is a research-action type of experience in higher education lived by a “learning community” conformed by teachers and students whose aim is to become fostering agents for sustainable development. The experience was carried out as part of the plan for teacher training in Preschool Education. This paper is the authors' Final Graduation Paper, a requirement to obtain a Licentiate degree in Preschool Education at the University of Costa Rica. The research began with a diagnosis that would lead to the implementation of an action plan that was organized and carried out jointly by the students and their teachers. The project finished with the participants' acceptance of some “environmental commitments”.